“Evaluación de dosis de tetra hormona en la producción de lechuga (lactuca sativa L.) variedad grand rapids waldeman'S strain, bajo condiciones agroclimáticas en la provincia de Lamas” - Pezo Vásquez, Ángel David (2014)
This research paper entitled "Evaluation of dose tetrahormona in the production of lettuce (Lactuca sativa) variety Grand Rapids Waldeman's under growing conditions in the province of Lamas", aimed to evaluate the effect of different doses of tetrahormona and determine the dose more effectively in growing lettuce using the variety Grand Rapids Waldeman's Strain and perform economic analysis of the treatments under study. Statistical design far randomized blocks (RCBD) was used with five treatments and four blocks, making a total of 20 experimental units. The results indicate that the application of higher doses (treatment four, 400 cc.ha-1), more efficient performance with 77,337.5 kg ha-1 was obtained, yielding a higher value of B I C of 0,95 and a return of 95,23%. lncreasing the dose of applications defined positive linel tetrahormona weight increase plant yield and kg.ha-1 . Keywords: Evaluation, dose tetrahormona, efficiency, profit, cost, units, experimental